The Place of Manakıbnames in Alevi-Bektashi Culture and Identity Formation - Yıldız, Harun (Journal of Alevism-Bektashism Studies, 2020)
Alevi-Bektashi understanding and culture, that have emerged with the Islamization of Turks, have a largely religious and mystical character in line with the historical development of Islamic culture. Although the historically common culture among the Alevi-Bektashi communities living in our country is mostly oral culture, it is also a fact that these communities have some written sources guiding their religious, social and cultural life, and therefore this culture has some written codes. Manâkibnâmes have a remarkable place among those written sources.It can be said that the manâkibnâmes, which are among the important sources of Islamic thought and Sufi mysticism tradition, are the basic foundational texts of Alevi-Bektashi thought, just like the texts of Buyruk. The fact that both traditional Alevism and Bektashism have formed their Sufi mystical character, which is their main nature, and their basic institutions from these texts, reveals a remarkable situation. Through these texts, which have more a Sufi mystical content, the important religious/Sufi mystical beliefs and values, such as Allah-Muhammad-Ali, four gates and forty stations, three sunnahs and seven fards (religious obligations) and the principle of “controlling your hand, tongue and waist”, has given Alevi-Bektashi understanding its essential character and identity over the centuries.There are many manâkibnâmes in Alevi-Bektashi culture, and Manâkib-i Hunkar Haci Bektash Veli stands out among them. Those manâkibnâmes have been read as sacred texts among Alevi-Bektashi communities for centuries. Therefore, in this paper, we will try to focus on the place of manâkibnâmes in this culture and identity formation with the general outline and slightly different aspects. In this framework, firstly we will establish the boundaries of the semantic world of manakibnames by specifying their place and meaning in Alevi-Bektashi cultural world and tradition. Then we will discuss from various aspects important manâkibnâmes, such as Valayatname of Abdal Musa and Hacim Sultan, and especially Manâkib-i Hunkar Haci Bektash Veli.
Keywords: Manâkibnâmes; ancient Turkish culture; Valayatname; Abdal Musa; Hacim Sultan